Oxidative stress status and lipid profiles of diabetic pregnant rats exposed to cigarette smoke - Souza, Maricelma da Silva Soares de [UNESP]; Sinzato, Yuri Karen [UNESP]; Lima, Paula Helena Ortiz [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP]; Damasceno, Débora Cristina [UNESP] (Reproductive Healthcare Ltd, 2010)
This study aimed to evaluate the oxidative stress status and the concentrations of triglycerides, cholesterol and total proteins of pregnant rats exposed to the association of diabetes and cigarette smoke. Female Wistar rats were randomly distributed in four experimental groups, according to presence or not of diabetes and the exposure or not to cigarette smoke. Diabetes was induced by streptozotocin (40 mg/kg i.v.) and exposure to cigarette smoke was for 30 min, twice a day, for 2 months. At day 21 of pregnancy, blood was collected for total protein, triglyceride, cholesterol and oxidative stress determinations. Data were analysed by ANOVA followed by Student-Newman-Keuls test (P < 0.05). The association of diabetes and exposure to cigarette smoke was related to the indidence of hypertriglyceridaemia, and this result was due to the severe diabetes and not to exposure to smoke. There was no alteration to protein metabolism in pregnant rats. Diabetes and cigarette smoke exposure led to the activation of the antioxidant system in an attempt to detoxify the organism in face of high lipid peroxidation, which can be characterized by the determination of reactive substances to thiobarbituric acid. (C) 2010, Reproductive Healthcare Ltd. Published by Elsevier Ltd. All rights reserved.
Keywords: antioxidant system; cholesterol; cigarette smoke; diabetes mellitus; triglycerides